1992
DOI: 10.1007/bf02179041
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of cytotoxic CD4+ T cell clones from cancer patients treated by local immunotherapy

Abstract: We have previously reported that the antitumor effect of OK-432, a Streptococcal preparation, is markedly augmented when injected intratumorally together with fibrinogen (Cancer, 69: 636-642, 1992). In order to elucidate the mechanism of the antitumor effects, we established T cell clones from regional lymph nodes of colorectal cancer patients who received this local immunotherapy. By culture of lymph node lymphocytes, in the presence of IL-2 and OK-432, 4 clones of T cells were established from 4 patients tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1993
1993
1997
1997

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…When we investigated the cytotoxicity of RLN lymphocytes, both the NK and LAK activity were found to be elevated in the RLN lymphocytes from the patients who had received the immunotherapy. The broad spectrum of cytotoxicity of RLN lymphocytes seems to be displayed mainly by CD4+T-cells proliferating in RLN, which is in line with our previous report that the cloned CD4+T-cells from RLN of OK-432/fbg-treated patients showed elevated killing activity against K562 and Daudi cells [32]. The cytotoxicity was highest in the lymphocytes of RLN adjacent to the tumor site, but the lymphocytes recovered from the RLN distant from the tumor site, also exhibited moderate degree of cytotoxicity.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…When we investigated the cytotoxicity of RLN lymphocytes, both the NK and LAK activity were found to be elevated in the RLN lymphocytes from the patients who had received the immunotherapy. The broad spectrum of cytotoxicity of RLN lymphocytes seems to be displayed mainly by CD4+T-cells proliferating in RLN, which is in line with our previous report that the cloned CD4+T-cells from RLN of OK-432/fbg-treated patients showed elevated killing activity against K562 and Daudi cells [32]. The cytotoxicity was highest in the lymphocytes of RLN adjacent to the tumor site, but the lymphocytes recovered from the RLN distant from the tumor site, also exhibited moderate degree of cytotoxicity.…”
Section: Discussionsupporting
confidence: 78%
“…These observations support our conclusion that the activation of both the B-lymphocytes and T-lymphocytes in RLN is triggered. We have previously reported that the B-lymphocytes from RLN of the patients who had received local immunotherapy with OK-432/ fbg could be a desirable source for the generation of human-human hybridomas [31], and cytotoxic T-cell clones could be established from the T-lymphocytes of the RLN [32]. The above-stated changes in morphology of RLN correlates well with the increased responsiveness of lymphocytes.…”
Section: Discussionmentioning
confidence: 77%
“…This type of local immunotherapy is effective not only in inducing local tumor regression but also in activating various cell components of regional lymph nodes [11]. Furthermore, we established cytotoxic CD4+T-cell clone and human monoclonal antibodies derived from such lymph nodes of cancer patients [12][13][14][15]. We have adminstered OK/fbg to 105 cases of colorectal cancer, about 90% of which subsequently displayed remarkable degrees of tumor necrosis.…”
Section: Introductionmentioning
confidence: 99%